Hypocretin-1 dose-dependently modulates maternal behaviour in mice - D’Anna, Kimberly L. (2006)
Increases in neuronal activity of hypocretin (HCRT), a peptide involved in arousal, and in HCRT-1 receptor mRNA expression have recently been identified in association with lactation. HCRT is released within brain regions regulating maternal behaviour and it is possible that increased HCRT neurotransmission during lactation supports maternal care. This study examined for the first time the behavioural effects of HCRT on lactating mice. At intermediate doses, intracerebroventricular (i.c.v.) injections of HCRT-1 (0.06 and 0.1 μg) elevated levels of licking and grooming of pups (but not self-grooming) and number of nursing bouts without affecting other behaviours. At the highest dose, i.c.v. HCRT-1 (0.3 μg) delayed latency to nurse, decreased nursing, increased time off nest, and decreased maternal aggression. Intraperitoneal injections of the HCRT-1 receptor antagonist, SB-334867, exhibited a general trend towards increasing time spent low-arched back nursing (p=0.053) and decreasing licking and grooming of pups while high-arched back nursing (p=0.052). This suggests that the endogenous release of HCRT, working independently or dependently with other neuromodulators, may be necessary for full maternal behaviour expression. Possible sites of HCRT action in enhancing and impairing maternal care were identified via examinations of c-Fos immunoreactivity in association with i.c.v. HCRT injections. Together, these finding support the idea of HCRT modulating maternal behaviour, with intermediate levels (0.06 and 0.1 μg) supporting, even augmenting some behaviours, but with levels too high (0.3 μg i.c.v. HCRT) maternal behaviour and aggression are suppressed.